Response of organic nitrogen in Black Soil to long-term different fertilization and tillage practices in Northeast China - Li YAN; Hui LI; Jinjing ZHANG; Zhidan ZHANG; Ping ZHU; Qiang GAO; Wenxi LU (Soil and Water Research, 2016)
A long-term (18 years) effect of different fertilization and tillage management practices- fallowing treatment (no fertilizer, no cultivation); CK (no fertilizer, cultivation); N (nitrogen fertilizer); NP (nitrogen and phosphorus fertilizer); NK (nitrogen and potassium fertilizer); PK (phosphorus and potassium fertilizer); NPK (nitrogen, phosphorus, and potassium fertilizer); M1NPK (chemical fertilizer plus manure); 1.5M1NPK (1.5 times M1NPK); NPKS (mineral fertilizer plus straw); Rot (3-year crop rotation of maize-maize-soybean with M1NPK), and M2NPK (2 times manure plus mineral fertilizer) - on the content of total nitrogen and organic forms of nitrogen and the nitrogen content in different particle-size fractions were studied in topsoil (0-20 cm) in Black Soil of NE China by using the methods of Bremner. The results showed that the combined application of organic and mineral fertilizers could significantly increase the contents and proportions of total nitrogen and organic nitrogen forms in soil. Comparing to CK treatment, the content of total nitrogen and hydrolyzable nitrogen increased in the fallow and organic materials treatments. Compared with M1NPK treatment, rotation was more beneficial to increasing organic nitrogen content, especially remarkably increasing amino acid nitrogen. The nitrogen response of sand, silt, and clay was most sensitive on manure; the effects of fallow and manure treatments on sand were notable, the nitrogen content in sand with NPKS increased by 40.86% compared with CK treatment. Our results imply that fallow/rotation managements, and manure/straw application can improve soil fertility.